Utilization of maternal health services among adolescent women in Bangladesh: a scoping review of the literature - Shahabuddin, A. S. M.; Delvaux, Therese; Abouchadi, Saloua; Sarker, Malabika; Brouwere, Vincent De (Tropical Medicine & International Health, 2016)
Includes bibliographical references (page 828-829).